2007
DOI: 10.1177/000313480707301201
|View full text |Cite
|
Sign up to set email alerts
|

Article Commentary: Diagnosis and Management of Extremity Compartment Syndromes: An Orthopaedic Perspective

Abstract: More than 200,000 people in the United States are diagnosed annually with compartment syndrome. This condition is commonly established based on clinical parameters. Determining its presence, however, can be challenging in obtunded patients or those with an altered mental status. A delay in diagnosis and treatment of these injuries can result in significant morbidity. Surgical release of the enveloping fascia remains the acceptable standard treatment for compartment syndrome. This article reviews the evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 30 publications
(18 reference statements)
1
23
0
Order By: Relevance
“…Interestingly, when looking at individual surgeons, the "more commonly a surgeon decided to check compartment pressures, the more likely the surgeon was to perform fasciotomy," 28 which introduces the hypothesis that a high false-positive rate may exist when using compartment checks. In addition, Prayson et al 29 30 Contrary to previous studies questioning the usefulness of compartment pressure measurements, McQueen et al 31 estimated the sensitivity and specificity to be high. In a large retrospective review of patients who sustained a tibial diaphyseal fracture and underwent documented continuous anterior compartment pressure monitoring, the sensitivity and specificity were estimated as 94% and 98%, respectively, and the positive and negative predictive values were 93% and 99%, respectively.…”
Section: Clinical Features and Diagnosismentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, when looking at individual surgeons, the "more commonly a surgeon decided to check compartment pressures, the more likely the surgeon was to perform fasciotomy," 28 which introduces the hypothesis that a high false-positive rate may exist when using compartment checks. In addition, Prayson et al 29 30 Contrary to previous studies questioning the usefulness of compartment pressure measurements, McQueen et al 31 estimated the sensitivity and specificity to be high. In a large retrospective review of patients who sustained a tibial diaphyseal fracture and underwent documented continuous anterior compartment pressure monitoring, the sensitivity and specificity were estimated as 94% and 98%, respectively, and the positive and negative predictive values were 93% and 99%, respectively.…”
Section: Clinical Features and Diagnosismentioning
confidence: 96%
“…Surgical decompression is not always indicated if the compartment syndrome has been evident for more than 48 hours and no evidence exists of retained function of the components within the compartment. 30 Timing of prophylactic fasciotomy is controversial, and outcome data comparing prophylactic vs therapeutic fasciotomy are retrospective and of mediocre quality. In a study of 94 patients (including trauma and vascular patients), Velmahos et al 44 found higher complication and nonclosure rates in n trauma update prophylactic fasciotomy cases.…”
Section: Treatment Fasciotomy and Outcomesmentioning
confidence: 99%
“…Usually, 5 "P" are associated with ACS, Pain, Paresthesia, Pallor, Paralysis, and high intra-compartment Pressure. Numbness, tingling and paresthesia are early signs 13 . Pain is severe and disproportionate to the injury or surgery, it is not relieved by painkillers and morphine, and it is worsen by passive stretch of compartment muscles.…”
Section: Diagnosismentioning
confidence: 99%
“…isointense to increased T1 signal intensity, increased T2 signal intensity, and homogeneous post-GBCA enhancement (►Fig. 14). The second pattern is described as homogeneous or heterogeneous T1 hyperintensity, heterogeneous T2 hyperintensity, and peripheral enhancement with the so-called stipple sign, defined as dotlike or linear streaky enhancement within an otherwise hypoenhancing muscle (►Fig.…”
Section: Rhabdomyolysismentioning
confidence: 99%
“…6,13 Treatment decisions should not be based on compartmental pressure measurements alone because this may lead to unnecessary surgery. 14 Imaging is most often utilized in situations of challenging clinical assessment or coexisting injury. 13 Radiographs are often initially obtained for evaluation of a suspected fracture.…”
mentioning
confidence: 99%